2018
DOI: 10.1111/jzo.12548
|View full text |Cite
|
Sign up to set email alerts
|

Differences in standard metabolic rate at the range edge versus the center of an expanding invasive population of Xenopus laevis in the West of France

Abstract: Empirical and theoretical studies have investigated the trade‐offs between reproduction, dispersal and/or survival that may arise between individuals at the range edge of an expanding population. The differential allocation of resources to these life‐history traits may then be constrained by the metabolism of an individual. Previous studies of an invasive expanding population of the frog Xenopus laevis in the West of France showed an increase in allocation of resources to dispersal and a decrease in allocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 77 publications
2
39
0
Order By: Relevance
“…3A-C). Previous studies (Louppe et al 2017(Louppe et al , 2018 have shown that individuals from the periphery have a greater stamina and a lower standard metabolic rate (SMR) for their body size. Larger muscles with longer fibres should result in greater power output and faster contractile velocity, traits that likely enhance jumping performance (James et al 2007).…”
Section: Muscle Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…3A-C). Previous studies (Louppe et al 2017(Louppe et al , 2018 have shown that individuals from the periphery have a greater stamina and a lower standard metabolic rate (SMR) for their body size. Larger muscles with longer fibres should result in greater power output and faster contractile velocity, traits that likely enhance jumping performance (James et al 2007).…”
Section: Muscle Architecturementioning
confidence: 99%
“…Consequently, differences in dispersal capacity between individuals from the centre and the front of the range should be reflected in traits that enhance dispersal capacity. Hind limb length has previously been demonstrated to be greater, for example, in animals from the range edge (Louppe et al 2017). However, whether other anatomical differences exist remains to be tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing number of biological invasions where spatial selection for a dispersal phenotype on the expanding front has been demonstrated. Morphological divergence of dispersal‐related traits in vanguard populations has been observed in amphibians, for example in Australia with the invasive cane toad ( Rhinella marina ) and in France with the invasive African clawed frog ( Xenopus laevis ) (Phillips et al ., ; Louppe, Courant & Herrel, ). Similarly, reduced parasite prevalence in range‐edge populations has been demonstrated with the blue striped snapper ( Lutjanus kasmira ) in Hawaii and the common house geckos ( Hemidactylus frenatus ) in Australia (Gaither et al ., ; Coates et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, we apply this conceptual model to juvenile life stages, a critically understudied life history stage that coincides with transitional movement from aquatic to terrestrial habitats (Cline & Hunter, ; Ramírez, Bell, Germano, Bishop, & Nelson, ; Roe & Grayson, ). Laboratory‐based quantification of individual performance measures, such as jumping ability, speed, and endurance, has been commonly used as proxies for individual dispersal and natural movement (Binning, Shaw, & Roche, ; Llewelyn, Phillips, Alford, Schwarzkopf, & Shine, ; Louppe, Courant, & Herrel, ; Phillips, Brown, Webb, & Shine, ). Body size and morphology have also been important determinants of individual performance and in some cases dispersal (John‐Alder & Morin, ; Yagi & Green, ).…”
Section: Introductionmentioning
confidence: 99%